Temperature-based phenology modeling and GIS-based risk mapping: A tool for forecasting potential changes in the abundance of Mealybug Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Fand, B.B.; Tonnang, Henri E.Z.; Kumar, M. Dinesh; Kamble, A.L.; Bal, S.K. (Springer, 2015)
Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is a highly invasive and a polyphagous pest of worldwide importance. Its recent outbreak and rapid spread in Indian cotton growing belt caused large scale devastation. A study was undertaken with a basic assumption that the future distribution and abundance of P. solenopsis will be affected seriously by temperature alterations due to global climate change, which might further aggravate the yield losses. This chapter describes a temperature-dependent simulation model predicting population growth potential of P. solenopsis under varied environmental conditions.